Assessing limited visibility feedback for overhead manufacturing assembly tasks. (November 2021) - Bhat, Prajna; Senft, Emmanuel; Zinn, Michael; Gleicher, Michael; Mutlu, Bilge; Cook, Rebecca; Radwin, Robert G.
Abstract: Worker posture, task time and performance are often affected when one-handed manual dexterous tasks are performed in small overhead spaces under an obscured view. A common method used for supplementing visual feedback in these cases is a hand-held telescopic mirror, but that involves working with both arms extended overhead, and is often accompanied by awkward neck and shoulder postures. A video camera was considered as an alternative to using a mirror for visual feedback and reducing overhead reach. A mirror, a borescope and an omnidirectional camera were evaluated while laboratory participants performed three one-handed simulated manufacturing tasks in a small overhead enclosure. Videos were recorded for quantifying the time that postures were assumed while performing the tasks. The average time that both arms were above mid-shoulder height for the omnidirectional camera was more than 2.5 times less than for the mirror and borescope. The average proportion of neck strain time was 0.01% (or less) for both the omnidirectional camera and the borescope, compared to 83.68% for the mirror. No significant differences were observed in task completion times between the three modalities. Hence, an omnidirectional camera can provide visibility while reducing straining postures for manufacturing operations involving overhead work. Highlights: The omnidirectional camera had less two-arm and neck strain times than the mirror and borescope. The omnidirectional camera had better usability compared to the mirror and borescope. No significant differences between modality task completion times were observed.